Solano-Altaba, María (2025). Pantallas, qué remedio. Cómo sobrevivir, con pensamiento crítico, al entorno digital, Ediciones Palabra, Madrid, ISBN 9788413684604. 256 pp. - Cabezuelo-Lorenzo, Francisco (Historia y Comunicación Social, 2025)
RESEÑA DE LIBRO